Profit efficiency of smallholder vegetable farms in Nepal: Implications for improving household income - Shrestha, Rudra Bahadur; Bhandari, Humnath; Pandey, Sushil (Frontiers Media, 2022)
Enhancing profit efficiency in vegetable farming is important to increase income, livelihoods, and nutrition security, and to reduce poverty of smallholder farmers, particularly in developing countries. This study examined the profit efficiency and its determinants in smallholder vegetable farms in Nepal using the stochastic translog profit function with cross-section data collected in 2013. The results revealed a high level of inefficiency in vegetable farms because of the combined effects of technical, allocative, and scale inefficiencies. The profitability differential in vegetable farms is significantly explained by input variables, namely, labor, land, seeds, fertilizer, pesticides, and capital. The determinants of profit inefficiency in vegetable farming were the types of crop varieties, access to information and extension services, access to agricultural credit, distance of farms to markets, and sex of farm manager. The profit efficiency in vegetable farming can be enhanced by adopting improved seed varieties, improving effective information and extension programs, increasing accessibility of credit facilities to the farmers, developing market infrastructure, and empowering women farmers in vegetable farming that leads to improve household income and nutrition security.